2014
DOI: 10.1007/s11606-014-3127-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Out-of-Pocket Spending Caps on Financial Burden of those with Group Health Insurance

Abstract: BACKGROUND:The Affordable Care Act (ACA) mandates that all private health insurance include outof-pocket spending caps. Insurance purchased through the ACA's Health Insurance Marketplace may qualify for income-based caps, whereas group insurance will not have income-based caps. Little is known about how out-of-pocket caps impact individuals' health care financial burden. OBJECTIVE: We aimed to estimate what proportion of non-elderly individuals with group insurance will benefit from out-of-pocket caps, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Future investigations perhaps should track the path from distal causes of population health (eg, political and economic factors) (18) to measures of diabetes maintenance. For example, in the complex and shifting world of health insurance, mechanisms such as "churning" in and out of coverage or increasing underinsurance though various out-of-pocket expenses (19)(20)(21)(22)(23) may explain patterns of incomplete care more than the simple type of payer does.…”
Section: Discussionmentioning
confidence: 99%
“…Future investigations perhaps should track the path from distal causes of population health (eg, political and economic factors) (18) to measures of diabetes maintenance. For example, in the complex and shifting world of health insurance, mechanisms such as "churning" in and out of coverage or increasing underinsurance though various out-of-pocket expenses (19)(20)(21)(22)(23) may explain patterns of incomplete care more than the simple type of payer does.…”
Section: Discussionmentioning
confidence: 99%
“…This accords with recent publications using unaffordability as a measure of financial barriers. 16 , 17 , 18 Exact MEPS questions used to compute the unaffordability metric are found in Online Appendix A .…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…Moreover, financial burden as a measure of underinsurance is problematic because the OOP caps under ACA make it mathematically impossible for some middleincome families to reach the 10% or 20% of income threshold, despite the possibility they may be significantly impacted by their medical expenses. 16 Previous work modeling avoided or delayed care only in families with children demonstrated that in such families, a measure of these concerns is a better predictor of unmet needs than raw OOP costs. 17 It is important to note that the concept of underinsurance includes components beyond the economic concerns of avoiding care due to cost and percentage of income spent on health care expenses mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…The US created a home care model, based on HST and refundable by the insurance agencies, that deals with both diagnosis and therapeutic care of OSAS patients. This services company, called the Affordable Care Act (ACA) aims to provide high quality healthcare to OSAS patients 49 50 . The ACA is gearing up towards a diagnostic model that focuses on the doctor-patient relationship.…”
Section: Health-care Providers and Models Of Care To Manage Osasmentioning
confidence: 99%